Internal Quality Assurance System Based on Islamic Organizational Culture in Strengthening Educational Quality in Islamic High Schools: A Systematic Literature Review - Safitri Agustina; Syafrimen Syafrimen; Tulus Suryanto; Koderi Koderi (Assyfa Journal of Islamic Studies, 2026)
Educational quality remains a strategic issue in the development of national education systems, including Islamic educational institutions. To promote continuous quality improvement, the Indonesian government has established the Internal Quality Assurance System (IQAS) as a key mechanism for quality control and enhancement at the institutional level. However, previous studies indicate that the implementation of IQAS in Islamic educational institutions often remains administrative and compliance-oriented, with limited integration into the organizational culture of schools. Consequently, Islamic organizational culture is increasingly recognized as a strategic foundation for strengthening quality culture and ensuring the effectiveness of quality assurance practices. This study aims to analyze, synthesize, and construct a conceptual model of an Internal Quality Assurance System based on Islamic organizational culture for strengthening educational quality in Islamic senior high schools. The study employs a Systematic Literature Review (SLR) approach following the PRISMA 2020 guidelines. Data sources consist of scholarly articles, academic books, and policy documents published between 2020 and 2026 and retrieved from Scopus, Dimensions, Crossref, Google Scholar, DOAJ, Garuda, and SINTA databases. The literature selection process followed the stages of identification, screening, eligibility assessment, and inclusion based on predetermined criteria. The findings indicate that the successful implementation of IQAS is influenced not only by technical and administrative aspects but also by organizational culture, leadership, stakeholder participation, and institutional commitment to quality. Islamic organizational culture, characterized by the values of amanah (trustworthiness), ihsan (excellence), itqan (professionalism), shura (consultation), adl (justice), ukhuwah (brotherhood), discipline, and exemplary leadership, demonstrates strong alignment with the principles of quality culture and continuous improvement. The integration of these Islamic values into the PPEPP cycle contributes to the development of a sustainable and contextually relevant quality culture within Islamic educational institutions. This study proposes a conceptual model positioning Islamic organizational culture as a cultural mechanism linking the implementation of IQAS to educational quality enhancement. The novelty of this study lies in integrating Internal Quality Assurance Systems, Islamic organizational culture, quality culture, and Islamic educational management into a comprehensive conceptual framework. The proposed model is expected to provide both theoretical and practical contributions to the advancement of quality assurance systems in Islamic education in Indonesia.